A Survey on Heart Attack Prediction Using Machine Learning - et. al., P.Santhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Machine Learning Algorithm is used for many different diseases. Machine Learning is a learning of machine by own itself. And it is a part of AI that deals with to learn a machine according to their own. Now-a-days most are affected due to Heart attack it becomes head ache for doctors. In order to reduce the count of death we need to predict the Heart attack. For this problem Machine Learning play a major role in this paper. This prediction takes a people from the danger zone of their life. In this paper we use KNN algorithm and Random forest algorithm can predict the heart attack in advance.